Vision, Reading Difficulties, and Visual Stress - Wilkins, Arnold J.; Evans, Bruce J. W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an overview of the research surrounding the relevance of visual factors for those who struggle with reading. Visual interventions that have been advocated as helping with reading include spectacles that simply correct refractive errors (e.g., long-sightedness), coloured overlays (sheets placed on the page) and coloured lenses, vision therapy, and computer games. This book explains the rationale behind these interventions and discusses the evidence supporting them. Clear advice is given in plain English to those wondering if these interventions will be helpful. Vision, Reading Difficulties, and Visual Stress, 2nd Edition draws together disparate research findings in a range of neurological disorders where vision is compromised by cortical hyperexcitability. Optometrists, orthoptists, ophthalmologists, educational psychologists, teachers, and vision scientists will find this book to be an interesting resource as well as students in these disciplines and parents of children who struggle with reading.
Introduction -- Refractive Errors And Ocular Health -- Binocular Vision And Accommodative Anomalies -- Controversial Vision Therapies -- Magnocellular Theories. Coloured Filters - Early Studies -- Do Coloured Filters Work? -- How Do Coloured Filters Work? -- Coloured Filters: Clinical Tools -- Clinical Protocol -- Other Potential Uses Of Colour -- The Future.
Keywords: Ophthalmology; Educational psychology; Ophthalmology; Educational Psychology; Vision Disorders -- diagnosis; Dyslexia -- diagnosis; Ophthalmology -- instrumentation